Design and Implementation of Digital Spirometer Using Arduino (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Spirometer is a medical diagnostic device used to evaluate the performance of the lungs through exhalation produced during the human breathing process. Through the MPX5010dp pressure sensor, the device can be practically applied. Using a tube of different diameters, it was connected to the sensor in each diameter. The sensor measures the pressure difference for both diameters when the pressure is applied inside the tube. This means when a person exhales inside the tube of different diameters, the sensor calculates the pressure difference applied inside the tube. Using the electronic controller Arduino UNO is received by the signal from the sensor blades software in the form of "volt" and it shows on the display LCD16 * 2.